THE APPLICATION OF PROJECT-BASED LEARNING MODEL IN TEACHING NEWS TEXT WRITING TO STUDENTS OF GRADE VIII OF STATE JUNIOR HIGH SCHOOL 1 KEDOKAN BUNDER - Depi, Depi; Mustamil, Mustamil; Fajri, Khoirul (Transpublika Publisher, 2023)
This research was prompted by students' lack of interest and motivation in writing news texts, their limited ability to compose such texts, an unsupportive learning environment, the use of less diverse teaching methods, and students' struggles to generate ideas and structure sentences into news texts. The research objectives include assessing the effectiveness of project-based learning in teaching news text writing to eighth-grade students at SMP Negeri 1 Kedokan Bunder and evaluating student engagement in the learning process using this model. The research employed an experimental approach with a quasi-experimental design (nonequivalent control group design). Statistical analysis, using an independent samples t-test, yielded a t-value of 4.313, which exceeded the t-table value of 1.669, leading to the rejection of H0 and acceptance of H1. This demonstrates the effectiveness of the project-based learning model in teaching news text writing to eighth-grade students at SMP Negeri 1 Kedokan Bunder. Additionally, observations in the experimental class revealed that students actively and effectively participated in the teaching and learning process using this model.